Assessment of asymmetry in pelvic motion – An inter- and intra-examiner reliability study. (June 2014) - Åström, Malin; Gummesson, Christina
Abstract Pelvic asymmetry has been suggested to change the biomechanics of the body and result in musculoskeletal pain. It is therefore of great relevance that there are tests that are reliable and valid when assessing pelvic asymmetry. The aim of this study was to examine the inter- and intra-examiner reliability for the standing flexion test (SFT), the initiation of the squat motion test (IOSMT) and the standing hip flexion test (SHFT), assessing asymmetry in pelvic motion around a transverse axis. Four experienced physiotherapists assessed in total 34 participants. Percentage agreement for inter-examiner reliability varied between 59% and 71% and kappa values between 0.2 and 0.4.The percentage agreement in intra-examiner reliability varied between 74% and 87% and kappa values between 0.4 and 0.7. A post hoc analysis of participants reporting low back and/or neck symptoms showed similar results in percentage agreement. A limitation in the present study was that the distribution of findings of pelvic mobility was skewed, which could have affected the kappa analysis. This study indicates in conclusion that SFT, IOSMT and SHFT may be reliable palpation tests in clinic settings. It is recommended that assessment of pelvic motion should include all three tests, since this showed higher reliability than when using the tests separately.